Electrospun Transdermal Patch for Contraceptive Hormone Delivery - Mofidfar, Mohammad; Prausnitz, Mark R. (Current Drug Delivery, 2019)
Background: A transdermal patch for delivery of Levonorgestrel (LNG) can be used for long-acting contraception. Objective: In this study, we designed and characterized a patch made of nonwoven electrospun microfibers comprised of Polycaprolactone (PCL) encapsulating LNG for slow release in a mineral oil matrix. Methods and Results: Scanning electron microscopy showed uniform, randomly oriented PCL fibers with large interconnected voids filled with mineral oil. Thermogravimetric analysis indicated that LNG loaded into PCL fibers had thermal stability up to 200°C. Differential Scanning Calorimetry suggested that LNG was dispersed in the electrospun fibers without interaction between the LNG and PCL, and without formation of drug crystals. Fourier Transform Infrared spectroscopy and X-ray diffraction results further supported the conclusion that there was no chemical drug–polymer interaction in LNGloaded fibers. Effective in vitro flux (i) from patches into mineral oil was 1.9 μgcm-2h-1, (ii) from mineral oil across porcine skin was 4.6 μgcm-2h-1 and (iii) from patches across porcine skin was 1.7 μgcm- 2h-1, indicating that transdermal delivery rate was controlled by a combination of the patch and the skin. Conclusion: The LNG-loaded patches demonstrated steady delivery of LNG across skin for up to 5 days in vitro. With additional development, LNG-loaded electrospun PCL patches could be used for long-acting contraception.
Keywords: polycaprolactone